Projekt IKARUS--zjistení incidence kostních príhod u karcinomu prsu: retrospektivní analýza nemocných dispenzarizovaných v onkologických centrech Ceské a Slovenské republiky - Fínek, J; Prausová, J; Cmejlová, V; Cwiertka, K; Svébisová, H; Vyzula, R; Holánek, M; Bodorová, M; Slavícek, L; Kubecová, M; Loukotková, L; Neumanová, R; et al. (Klinicka onkologie, 2009)
BACKGROUND: Bone incidents today represent, in terms of frequency and the overall effect on the quality of life of patients with breast cancer, a serious health problem. In a number of clinical studies bisphosphonates have been shown to have a positive impact on reducing the risk of bone events and therefore to be effective in the prevention of bone events. The primary objective of this project was to identify the incidence of bone events in patients with metastatic breast cancer treated in the Czech and Slovak Republics. SUBJECTS: Retrospective, multi-centre, non-interventional, epidemiological and explorative studies to identify the incidence of bone events in the defined group of patients and a description of the practice of prevention and treatment of skeletal events in the years 2000-2005. Enrolled were patients with advanced metastatic breast cancer diagnosed in 2000. METHODS AND RESULTS: Analysis of overall survival and survival to disease progression, analysis of patterns of treatment of bone events and the practice of the use of bisphosphonates in the prevention of bone events in metastatic skeleton affection in the normal conditions of clinical practice, analysis of patient compliance in the treatment with bisphosphonates, analysis of the time interval between the occurrence of bone metastases and the occurrence of bone events and, last but not least, survival analysis of patients in relation to bone events. CONCLUSION: This work has shown that the practice of treatment with bisphosphonates since 2000 and assessed the survival of patients with metastatic breast cancer.
Keywords: Humans; nádory kostí; lidé středního věku; Bone Neoplasms; Aged; Female; dospělí; senioři; lidé; Slovakia; Slovenská republika; Adult; Breast Neoplasms; ženské pohlaví; Middle Aged; incidence; Incidence; Czech Republic; Aged, 80 and over; nádory prsu; senioři nad 80 let; Česká republika; bisfosfonáty; Diphosphonates